Resolution Enhancement in Model Resistivity using the Data Levels Amalgamation Technique for Groundwater Exploration - Bery, Andy Anderson (Research India Publications, 2016)
In the past few years, significant effort has been made in developing field data acquisition in electrical resistivity tomography (ERT) method. This paper presents development of the data level amalgamation (DLA) technique in resistivity data processing. This technique carried out using two different optimized arrays. They are Wenner-Schlumberger and Pole-Dipole arrays. These two arrays is chosen after made full consideration in terms of the signal strength, total number of datum points, sensitivity changes and lastly investigation depth. The real field study for the DLA technique verification was carried out at Taiping, Perak, Malaysia. The objective of field study at this area is related to groundwater exploration. Based on the application of the DLA technique in the field study, it showed that this technique is capable in resolution enhancement in model resistivity with topography results. The DLA technique is useful in increase the technical merit of this geophysical method for Earth’s subsurface imaging.